Design of Intelligent Foam Drainage Equipment with UAV Automatic Agent Replenishment for Low-Pressure Gas Wells: An Electromechanical System - Wu, Boya; Li, Benjie; Xiong, Yiqin (Scientific Journal of Technology, 2026)
In the mid-to-late production stages of low-pressure gas wells, wellbore liquid loading becomes a prominent issue. Traditional manual foam drainage agent injection suffers from inaccuracies in timing, agent waste, and high labor intensity. This paper presents the design of an intelligent foam drainage system integrated with UAV-based automatic agent replenishment, achieving core functions such as automatic precise injection, closed-loop control of concentration and flow rate, remote monitoring, and unmanned UAV agent replenishment. The equipment adopts a skid-mounted integrated structure and features an innovatively designed purely mechanical passive UAV-to-equipment liquid docking module. The electrical control system is centered on the STM32F103C8T6 microcontroller and incorporates the FreeRTOS real-time operating system to enable multitasking scheduling. The injection control employs a PID algorithm, with a first-order system model established that accounts for wellhead pressure disturbances; simulation results verify its fast response and strong disturbance rejection capability. Cloud-edge communication is implemented using the MQTT protocol to connect to the Alibaba Cloud IoT platform, enabling real-time data uploading and remote command issuance. Results demonstrate that this design significantly improves foam drainage efficiency, reduces agent consumption and labor costs, and is well-suited for long-term unattended operation in remote gas wells.